O009/#418 Next generation sequencing reveals a high prevalence of pathogenic mutations in homologous recombination DNA damage repair genes among patients with uterine sarcoma. (4th December 2022) - Nasioudis, Dimitrios; Latif, Nawar; Ko, Emily; Cory, Lori; Haggerty, Ashley; Kim, Sarah; Morgan, Mark; Simpkins, Fiona; Ii, Robert Giuntoli
Abstract : Objectives: Evaluate the prevalence of alterations in homologous recombination DNA damage repair genes (HR-DDR) among patients with uterine sarcomas. Methods: The AACR GENIE v12.0 database was accessed and patients with uterine leiomyosarcoma, adenosarcoma and endometrial stromal sarcoma were identified. We examined the incidence of pathogenic alterations of genes involved in HR-DDR: ATM, ARID1A, ATRX, BAP1, BARD1, BLM, BRCA2, BRCA1, BRIP1, CHEK2, CHEK1, FANCA, FANCC, FANCD2, FANCE, FANCF, FANCG, FANCL, MRE11, NBN, PALB2, RAD50, RAD51, RAD51B, RAD51C, RAD51D, WRN. Results: A total of 433 patients contributing to 450 samples were identified; 298 patients with leiomyosarcoma (LMS), 53 patients with adenosarcoma (AS), 30 patients with low-grade endometrial stromal sarcoma (ESS), 19 patients with high-grade, and 34 patients with ESS not specified (34 samples). The overall incidence of pathogenic HR-DDR gene alterations was 30% (135/450). The most prevalent gene alteration was ATRX (20%, 84/419) followed by BRCA2 (5%, 20/416), RAD51B (4%, 10/271), ATM (2.2%, 10/446) and ARID1A (1.9%, 8/419). The highest incidence of HR-DDR gene alterations was observed in leiomyosarcoma (36.5%) followed by adenosarcoma (29.8%), and HG-ESS (26.3%) while HR-DDR gene alterations were less common in ESS NOS (17.7%) and LG-ESS (13.3%). In the present cohort, incidence of TP53 mutations was 49% (213/432), while other common pathogenic gene alterations included the RB1 (29%, 128/449), PTEN (13%, 58/449) and MED12 (11%, 42/375) genes. Conclusions: Approximately 1 in 3 patients with uterine sarcoma, harbor a pathogenic alteration in HR-DDR genes. These results provide further rationale for the design of molecularly driven clinical trials exploring agents targeting DNA damage repair.